Critical success model for automation and robotics in Malaysian industrialised building system (IBS) / Mohd Najib Abd Rashid - Abd Rashid, Mohd Najib (2022)
The use of automation and robotics in industrialised building systems IBS commonly deals with uncertainties and complexity, thus requiring particular strategies to foster successful results. Despite the support and assistance from various government departments and private sector for the development of automation and robotics in IBS, it has been the subject of very few studies. Nevertheless, there is an increasing awareness among the IBS stakeholders of the use of automation and robotics to influence IBS projects success. This study aims to develop a critical success model based on the factors influencing the implementation of automation and robotics in IBS as view by IBS stakeholders in the Klang valley. In order to achieve this research aim, the first research objective is to identify the critical success factors (CSFs) for automation and robotics in IBS. The second research objective is to determine the success criteria of automation and robotics in IBS. Finally, the third research objective is to examine the relationship of the CSFs and the success of automation and robotics in IBS, simultaneously develop a critical success model for automation and robotics in IBS. This research adopts a quantitative approach to developing a conceptual framework for the factors influencing the use of automation and robotics in IBS through a literature review and questionnaire survey. The survey results were used to establish the critical success factors (CSFs) for automation and robotics in IBS and a structural equation modelling developed by using Smart-PLS version 3.2.7. In addressing the research aims, this study identifies four CSFs elements towards the success of automation and robotics in IBS: Strategy, People, Process and Technology. From the analysis, the top five factors in Strategy are: cost evaluation, risk assessment, economies of scale (EOS), government policies and vision. The top five factors for People are: technical capability, training, highly skilled, education, and an experienced workforce. For Process, the top five factors are: continuous improvement, coordination of design, transportation and installation, standardisation, modular design, and good working collaboration, and in Technology the top five factors are: Computer-aided design (CAD), information and communication technology (ICT), computer-aided manufacturing (CAM), building information modeling (BIM), computer numerical control (CNC). Furthermore, this study also identifies the top ten success criteria for automation and robotics in IBS: reduced construction and production time, reduced waste, reduced material consumption, improved occupational safety and health, improved working conditions, increased productivity, recycled waste material, workforce reduction and a high-quality product. Additionally, the research explores the impacts of critical success factors linked to automation and robotics' success in IBS by examining the standardized coefficient among the factors in the Partial Least SquareStructural Equation Modeling PLS-SEM. The finding indicates that Strategy, Process and Technology have a significant relationship on the success of automation and robotics in IBS. However, the People element was found to be statistically insignificant relationship, thus suggesting the moderating role for this element as a topic for future research. Finally, the research offers methodological and practical contribution as well as an opportunity for future research